Expert SQL Server 2008 Encryption - Coles, Michael; Landrum, Rodney (Apress : Imprint: Apress, 2009)
Every day, organizations large and small fall victim to attacks on their data. Encryption provides a shield to help defend against intruders. Because of increasing pressure from government regulators, consumers, and the business community at large, the job descriptions of SQL DBAs and developers are expanding to include encryption. Expert SQL Server 2008 Encryption will show you how to efficiently implement SQL Server 2008 encryption functionality and features to secure your organizational data. Introduces encryption, guiding readers through its implementation in SQL Server Demonstrates advanced techniques such as the use of hardware security modules Covers all that a SQL Server database administrator needs to know about encryption.